Enhanced excitonic emission efficiency in porous GaN. Issue 1 (December 2018) - Ngo, Thi; Gil, Bernard; Shubina, Tatiana; Damilano, Benjamin; Vezian, Stéphane; Valvin, Pierre; Massies, Jean
Abstract We investigate the optical properties of porous GaN films of different porosities, focusing on the behaviors of the excitonic features in time-integrated and time-resolved photoluminescence. A substantial enhancement of both excitonic emission intensity and recombination rate, along with insignificant intensity weakening under temperature rise, is observed in the porous GaN films. These observations are in line with (i ) the local concentration of electric field at GaN nanoparticles and pores due to the depolarization effect, (ii ) the efficient light extraction from the nanoparticles. Besides, the porosification enlarges the surface of the air/semiconductor interface, which further promotes the extraction efficiency and suppresses non-radiative recombination channels. Our findings open a way to increasing the emission efficiency of nanophotonic devices based on porous GaN.